2013
DOI: 10.1016/j.eurpolymj.2012.12.012
|View full text |Cite
|
Sign up to set email alerts
|

Effect of slight crosslinking on the mechanical relaxation behavior of poly(2-ethoxyethyl methacrylate) chains

Abstract: Elsevier Carsí Rosique, M.; Sanchis Sánchez, MJ.; Díaz Calleja, R.; Riande, E.; Nugent, MJD. (2013). Effect of slight crosslinking on the mechanical relaxation behavior of poly(2-ethoxyethyl methacrylate) chains. Abstract The synthesis, thermal and mechanical characterizations of uncrosslinked and lightly crosslinked poly(2-ethoxyethyl methacrylate) are reported. The uncrosslinked poly(2-ethoxyethyl methacrylate) exhibits in the glassy state two relaxations called in increasing order of temperature, the gamma … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 63 publications
(45 reference statements)
1
8
0
Order By: Relevance
“…The homopolymer from found that the cross-linking may produce different effects in the sub-glass transitions, which may be related to their molecular origin. [17][18][19][20][21][22][23] Thus, the secondary relaxations can have (i) an intramolecular origin, which involves the independent motion of an isolated group or (ii) an intermolecular origin, which involves the motion of essentially the entire molecule (repeat unit in the case of a polymer). The latter are known as Johari-Goldstein (JG) relaxations.…”
Section: Introductionmentioning
confidence: 99%
“…The homopolymer from found that the cross-linking may produce different effects in the sub-glass transitions, which may be related to their molecular origin. [17][18][19][20][21][22][23] Thus, the secondary relaxations can have (i) an intramolecular origin, which involves the independent motion of an isolated group or (ii) an intermolecular origin, which involves the motion of essentially the entire molecule (repeat unit in the case of a polymer). The latter are known as Johari-Goldstein (JG) relaxations.…”
Section: Introductionmentioning
confidence: 99%
“…This behavior has been observed in some systems where the formation of nanodomains, integrated by the side chains flanked by the backbone, is produced (Carsí, et al, 2012;Carsí, et al, 2013). This effect can be understood due to a decrease in the free volume.…”
Section: Dielectric Measurementsmentioning
confidence: 62%
“…The dynamic mechanical and dielectric properties are intrinsically correlated and they are associated with a structural polymer feature (McCrum, et al, 1991;Sanchis, et al, 1999;Carsí, et al, 2012;Carsí, et al, 2013;Deutsch, et al, 1954). The dynamic relaxation properties of cross-linked polymer networks are highly sensitive to network composition and polymer chain architecture.…”
Section: Mechanical Propertiesmentioning
confidence: 99%
See 2 more Smart Citations